A Stylistic Analysis of Selected Verses from Hafez Ibrahim’s Diwan (Journal of the College of Basic Education, 2026)
This study aims to conduct a stylistic analysis of selected verses from Hafez Ibrahim’s Diwan, focusing on the phonetic, semantic, and syntactic levels of the text. At the phonetic level, both internal and external rhythms of the verses were analyzed to examine their contribution to the musical aesthetic of the poetry. The semantic level focused on the use of simile, metaphor, and metonymy, highlighting the symbolic and conceptual depth of the poems. At the syntactic/constructive level, the study analyzed declarative and imperative sentences and their role in shaping meaning and conveying the message in an artful manner.The analysis revealed that Hafez Ibrahim skillfully combines internal and external sound harmony, precise use of rhetorical devices, and flexible syntactic structures, reflecting his ability to enhance meaning, rhythm, and stylistic impact in his poetic texts.